'A WONDERFULL MONSTER BORNE IN GERMANY': HAIRY GIRLS IN MEDIEVAL AND EARLY MODERN GERMAN BOOK, COURT AND PERFORMANCE CULTURE1. (October 2014) - Katritzky, M. A.; Woodford, Charlotte; Colvin, Sarah
ABSTRACT Human hirsuteness, or pathological hair growth, can be symptomatic of various conditions, including genetic mutation or inheritance, and some cancers and hormonal disturbances. Modern investigations into hirsuteness were initiated by nineteenth‐century German physicians. Most early modern European cases of hypertrichosis (genetically determined all‐over body and facial hair) involve German‐speaking parentage or patronage, and are documented in German print culture. Through the Wild Man tradition, modern historians routinely link early modern reception of historical hypertrichosis cases to issues of ethnicity without, however, recognising early modern awareness of links between temporary hirsuteness and the pathological nexus of starvation and anorexia. Here, four cases of hirsute females are reconsidered with reference to this medical perspective, and to texts and images uncovered by my current research at the Herzog August Library and German archives. One concerns an Italian girl taken to Prague in 1355 by the Holy Roman Empress, Anna von Schweidnitz. Another focuses on Madeleine and Antonietta Gonzalez, daughters of the 'Wild Man' of Tenerife, documented at German courts in the 1580s. The third and fourth cases consider the medieval bearded Sankt Kümmernis (also known as St Wilgefortis or St Uncumber), and the seventeenth‐century Bavarian fairground performer Barbara Urslerin.